(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
Female labour force participation (FLFP) is key to economic growth and gender equality. It also boosts the economy. FLFP rates vary widely amongst countries, with emerging nations having lower rates. FLFP’s economic and social advantages in emerging countries are also discussed. It also shows FLFP research in emerging countries. First, FLFP measures economic growth and gender equality. Second, FLFP research may help policymakers create FLFP-promoting policies and initiatives that reap economic and social advantages. Thirdly, FLFP research may help organizations understand female workers’ needs and create FLFPfriendly workplace regulations.